Ethnobotany, morphology and genotyping of cassava germplasm from Malawi - Benesi, I.R.M.; Labuschagne, Maryke T.; Herselman, L.; Mahungu, N.M. (2010)
The objectives of this study were to collect and characterise Malawian cassava germplasm using ethnobotany, morphological and Amplified Fragment Length Polymorphism (AFLP) markers. Exploration of accessions with the help of indigenous knowledge was done. Ninety three accessions collected from farmers fields and commercial programs were planted and morphologically characterised at Chitedze Agricultural Research Station (Malawi). A subsample of 28 accessions was used for DNA fingerprinting. Preferences of farmers for traits in cassava varieties were diverse according to use and areas. Ethnobotany revealed wide genetic diversity in the germplasm, as did morphological characterisation, but morphological characterisation failed to uniquely differentiate all analysed accessions. AFLP markers showed narrow genetic diversity but managed to distinguish all accessions. Hence, there is need to use all three techniques at different levels to identify genetic diversity.